Overview of the Causes of Self-Care Deficit Disorder: Musculoskeletal Disorders in The Elderly in Kendal Indonesia - Anggraeni, Rina; Virdayanti, Lilis; Jati, Riani Pradara; Aeni, Qurrotul; Nurwijayanti, Andriyani Mustika (GLOBAL HEALTH SCIENCE GROUP, 2023)
The increasing number of elderly will affect various aspects of elderly life, especially in terms of health and welfare of the elderly. Problems that arise make the ability to do activities decrease, one of which is the ability to perform self-care. Factors that cause a person to experience a self-care deficit include musculoskeletal disorders, neuromuscular disorders, weakness, psychological disorders and decreased motivation/interest. This study aims to describe the causes of self-care deficit disorder in the elderly in Cepiring. The type of research method chosen is descriptive analysis. The sample used using purposive sampling technique. The sample in this study were 86 respondents aged 60-80 years and experiencing self-care deficits. Data collection in this study used the Standard Nordic Questionnaire (SNQ). Data analysis uses frequency distribution to determine the number of musculoskeletal disorders. The results of the study most of the respondents experienced low Musculoskeletal Disorders as many as 46 (53.5%) respondents.